The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.2135/cropsci2013.11.0795
|View full text |Cite
|
Sign up to set email alerts
|

Oil Yield Components of Maize Crops Exposed to Heat Stress during Early and Late Grain‐Filling Stages

Abstract: Heat stress frequently limits grain yield of summer crops. Most research on maize (Zea mays L.) has analyzed heat stress effects on crop physiology and kernel set but little attention has been given to kernel weight and its composition. The objectives of this work were (i) to assess the response of maize oil yield components (kernel number and weight, embryo oil concentration, and embryo/kernel ratio) to postflowering heat stress and (ii) to explore changes in the sensitivity to this constraint across developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 69 publications
(119 reference statements)
1
32
0
Order By: Relevance
“…This also indicates that for every 1 • C rise in temperature, the yields of wheat soybean, mustard, groundnut and potato would decline by 3-7% in India [49]. Maize is also highly susceptible to heat stress during the reproductive stage [7,[50][51][52], and it is reported that each degree increase in a day where the temperature exceeds 30 • C reduces the final yield of maize by 1% under favorable growing conditions, and by 1.7% under drought-stressed conditions [53]. This shows that heat stress will be a major climate risk for crop production across Bihar, particularly for winterand spring-sown crops when higher temperatures coincide with the reproductive phase of the crops.…”
Section: Temperature Changes and Implications For Crop Productionmentioning
confidence: 99%
“…This also indicates that for every 1 • C rise in temperature, the yields of wheat soybean, mustard, groundnut and potato would decline by 3-7% in India [49]. Maize is also highly susceptible to heat stress during the reproductive stage [7,[50][51][52], and it is reported that each degree increase in a day where the temperature exceeds 30 • C reduces the final yield of maize by 1% under favorable growing conditions, and by 1.7% under drought-stressed conditions [53]. This shows that heat stress will be a major climate risk for crop production across Bihar, particularly for winterand spring-sown crops when higher temperatures coincide with the reproductive phase of the crops.…”
Section: Temperature Changes and Implications For Crop Productionmentioning
confidence: 99%
“…Treatments included a combination of four maize hybrids (H) with distinctive endosperm types (Flint: orange-flint; Pop: popcorn; Te: temperate semi-dent, and TeTr: temperate × tropical semi-dent) and two temperature regimes (TR) applied at daytime hours (non-heated control and heated) during two different growth stages (GS) of the effective grain-filling period (early and late) of 15-d duration. More details about the crop husbandry can be found in Mayer et al (2014). In both Exp, a single stand density of 9 plants m -2 was used.…”
Section: Crop Husbandry and Treatment Descriptionsmentioning
confidence: 99%
“…Kernel starch or protein concentration (in mg g -1 ) was expressed on a dry weight basis. More details about TRs can be found in Table 1 in Mayer et al (2014). After near infra-red transmittance analysis, at least a 20-g bulk of kernels from each sample was used to determine individual endosperm weight.…”
Section: Final Starch and Protein Concentration Of Kernels And Endospmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with previous reports that indicated that rainfall directly influenced the total production of maize due to increases in the distribution, density and depth of the roots (37) . Moreover, extreme temperatures affect directly the grain weight (38,39) and yield (40)(41)(42)(43) . Heat stress reduced maize grain weight due to proportional losses in grain composition (starch, protein and oil contents) and due to its direct effect during the grain-filling period, which caused a cessation of grain filling (43)(44) .…”
Section: Discussionmentioning
confidence: 99%